Hardware Implementation of a Neural Network for Plasma Position Control in Compass-D - Bishop, Christopher; Haynes, P. S.; Roach, C. M.; Todd, T. N.; Trotman, D. L.; Smith, M. E. U. (Proceedings of the 17th Symposium on Fusion Technology, Rome, Italy, 1992)
Proceedings of the 17th Symposium On Fusion Technology, Rome, Italy